Family and social change in Socialist and Post-Socialist societies : change and continuity in Eastern Europe and East Asia - Rajkai, Zsombor (Intimate and the public in Asian and global perspectives, 2015)
This volume reveals new dimensions of modernisation, by discussing the current social transformation of six Central and Eastern European countries as well as two East Asian societies seen through family and social change.